The Interrelations of Nature and Woman in Takahata's The Tale of The Princess Kaguya: An Ecofeminist Perspective - Lalita Tandayu; Hirmawan Wijanarka (Journal of Language and Literature, 2023)
Nature, as an essential part of human life, should be preserved to maintain a good quality of life for living beings, and literature can be a tool to promote this issue. This article aims at (1) exploring the characters in Isao Takahata's The Tale of the Princess Kaguya and (2) analyzing the interrelations of woman and nature as parallel in a patriarchal society. In discussing the movie, this article employs the ecofeminist approach. Five theories are applied to support the analysis: the theory of characterization and Mise en Scène, the theory of ecofeminism, the theory of symbolism, and the theory of patriarchy. The Tale of the Princess Kaguya reveals the equation of women and nature and how both are devalued. The analysis of the characters reveals that Princess Kaguya possesses caring, adventurous, and mysterious characteristics, while Sanuki no Miyatsuko possesses caring, loving, ambitious, and arrogant characteristics. The analysis also finds that Princess Kaguya loves to play with nature. She is equated to an animal, such as a bird, and a plant which is a tree branch. Women and nature are seen as parallel in the story. On the other hand, the noblemen in the story, as the masculine, are ignorant of nature as they pluck flowers and destroy a swallow's nest. This study finds out that Princess Kaguya experiences oppression as she is forced into a lifestyle she does not wish for and is harassed by an Emperor.